Superconductivity enhancement in FeSe/SrTiO3: a review from the perspective of electron–phonon coupling. (27th May 2020) - Xu, Xiaofeng; Zhang, Shuyuan; Zhu, Xuetao; Guo, Jiandong
Abstract: Single-layer FeSe films grown on SrTiO3, with the highest superconducting transition temperature ( T C ) among all the iron-based superconductors, serves as an ideal platform for studying the microscopic mechanisms of high- T C superconductivity. The significant role of interfacial coupling has been widely recognized, while the precise nature of the T C enhancement remains open. In this review, we focus on the investigations of the interfacial coupling in FeSe/SrTiO3 from the perspective of electron–phonon coupling (EPC). The main content will include an overview of the experimental measurements associated with different theoretical models and arguments about the EPC. Especially, besides the discussions of EPC based on the measurements of electronic states, we will emphasize the analyses based on phonon measurements. A uniform picture about the nature of the EPC and its relation to the T C enhancement in FeSe/SrTiO3 has still not achieved, which should be the key for further studies aiming to the in-depth understanding of high- T C superconductivity and the discovery of new superconductors with even enhanced T C .